The value of a collaborative community of practice to disseminate an inclusive pedagogy in a UK university - Alison Cornforth (Journal of Learning Development in Higher Education, 2025)
Collaboration between academic and professional support colleagues, including those working between roles or third space professionals, is essential to develop ongoing teaching practice in higher education (HE). From the perspective of a ‘third space professional’, this study evaluates the value of a university-wide collaboratively developed website as an inclusive Community of Practice (CoP) in a post-1992 university. The website aimed to share inclusive teaching resources, designed in previous practice, and initiatives for colleagues new to teaching, with the purpose of supporting new Professional Standards Framework (PSF) (AdvanceHE, 2023) criteria. A small-scale case study approach was taken using mixed methods of semi-structured interviews and pre and post launch website data analytics to triangulate and analyse data. The existence, benefits and challenges in collaboration between professional support and academic colleagues were evaluated. The value of the website was also analysed as a model to build collaboration as a CoP to promote teaching development and disseminate an inclusive pedagogy. Although the will to collaborate was identified, alongside increased recognition of professional colleagues’ credentials, opportunities to collaborate were reduced due to workloads, time and a research-intensive culture where teaching initiatives and collaborations were less valued.  This study suggests that third space professionals can promote value in teaching development in Education Developer roles by increasing the Scholarship of Teaching and Learning (SoTL) and designing theory-based teaching resources to support academic workloads and encourage collaboration.